2020
DOI: 10.15376/biores.15.4.9596-9610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermo-hydro-mechanical treatments on various physical and mechanical properties of poplar (Populus) wood

Abstract: Poplar (Populus) wood was subjected in this work to thermo-hydro-mechanical treatment. The influence of the treatment parameters on the physical and mechanical properties were investigated. The wood samples were densified under three compression ratios (0%, 30%, and 50%), and thermally treated at three temperatures (180 °C, 200 °C, and 220 °C), at three thermal treatment durations (3 h, 4 h, and 5 h). The density, modulus of elasticity, modulus of rupture, radial hardness, and thickness swelling were measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Although this is a positive effect, dimensional stability could be standardized by a detailed study of the thermal variable of the process without including an additional step. It has been reported that the thermal phase provides better dimensional stability to the densi ed wood 54 , but it also has signi cant adverse effects on the physical and mechanical properties of the wood due to the degradation of its chemical components 55 . Finally, it is important to mention that total immersion tests were also performed for 24 h, nevertheless, the results of these tests were not statistically conclusive and, so they were not included in the present work.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Although this is a positive effect, dimensional stability could be standardized by a detailed study of the thermal variable of the process without including an additional step. It has been reported that the thermal phase provides better dimensional stability to the densi ed wood 54 , but it also has signi cant adverse effects on the physical and mechanical properties of the wood due to the degradation of its chemical components 55 . Finally, it is important to mention that total immersion tests were also performed for 24 h, nevertheless, the results of these tests were not statistically conclusive and, so they were not included in the present work.…”
Section: Physical Propertiesmentioning
confidence: 99%